Climatic limits to headwall retreat in the Khumbu Himalaya, eastern Nepal - Scherler, Dirk (Geology, 2014)
Ice-free bedrock headwalls are widespread landforms of many glacial landscapes, but their formation and evolution are not well understood. Here, I present observations from the Khumbu Himalaya, eastern Nepal, of a distinct elevation zone that aligns the base of many steep headwalls with the highest predicted frost-cracking intensity (FCI). Below this zone, median ice-free hillslope angles are ≤40° and similar to those of other areas in the Himalaya, where threshold hillslopes that are close to the critical angle of stability have been inferred. At higher elevations, ice-free hillslopes of different rock types have median slope angles of ∼50°–55°, suggesting threshold hillslopes with higher rock mass strength, possibly related to the presence of deep-reaching permafrost. High-altitude meteorological data combined with FCI models support frost cracking as a mechanism for headwall retreat by undercutting of threshold headwalls, while glacial transport inhibits the accumulation of scree deposits at their base. This mechanism could account for continued headwall retreat as long as climatic conditions enable frost cracking near the base of headwalls that are high enough to sustain glaciers at their base, even if subglacial erosion is minor.